Power Quality Analysis Of A 20 Kv Medium Voltage System Using Fft And Wavelet Analysis Methods - M. Irwansyah; Beni Satria; Ahmad Dani (International Journal of Economic, Technology and Social Sciences (Injects), 2024)
This study aims to analyze the power quality in a 20 kV medium voltage distribution system (voltage 20 kV, frequency 50 Hz, line length 5 km, input power 185 kVA, load 95 kW, pf 0.75) experiencing 3rd (10%) and 5th (5%) harmonic disturbances, as well as momentary voltage increases. The goal is to detect disturbances and neutralize them to restore the voltage waveform to a pure sine wave. The combined method of Fast Fourier Transform (FFT) and Wavelet is used through MATLAB simulation. FFT detects harmonics in the frequency domain, while Discrete Wavelet Transform (DWT) analyzes momentary voltage changes in the time-frequency domain. Simulations are performed with active harmonics at 0.2-0.4 seconds (sampling rate 1000 Hz), validated with real system characteristics. As a result, FFT identified harmonics of 150 Hz (2,828 kV) and 250 Hz (1,414 kV) with THD of 11.2%, while Wavelet detected the fault time. Neutralization using passive filters (150 Hz and 250 Hz) and capacitor banks (52.54 kVAR) reduced the THD < 5%, returning the voltage to 28.28 kV pure sine. This study offers a comprehensive analysis and practical solutions to improve the reliability of the distribution system, with suggestions for field data validation for further improvement.